Contribution of nuts for the daily intake of salt, fat and fatty acids - Albuquerque, T.G. (2019)
Nuts are rich sources of unsaturated fatty acids, which link the consumption of these types of foods with decreased incidence of cardiovascular disease, due to blood cholesterol levels reduction. Besides having a favourable fatty acid profile, nowadays several nuts are processed (roasted or fried) and other ingredients are added such as salt, honey, spices and aromatic plants, which can influence their nutritional quality. Therefore, in this study the determination of salt, fat and fatty acids composition of 16 processed nuts was used to assess their contribution for the daily intake of the above-mentioned nutrients and evaluate their impact on public health. Samples of almonds, cashews, peanuts, corn, broad beans or mixtures of different nuts, widely available in the market, were collected in supermarkets. Total fat determination was performed by acid hydrolysis method followed by Soxhlet’s extraction with petroleum ether. The salt content was determined by Charpentier Volhard’s titration. Preparation of fatty acids methyl esters was carried out by a combined method of methylation and transesterification, followed by gas chromatography analysis coupled with flame ionization detector. Regulation (EU) No. 1169/2011 was used to estimate the contribution of a portion (35 g) of nuts for the daily intake, for an adult, of salt (6 g/day), fat (70 g/day) and saturated fatty acids (20 g/day). Total fat content in the analysed nuts varied between 12.2 ± 0.31 and 53.6 ± 0.49 g/100 g, while the salt content ranged from 0.24 to 2.69 g/100 g. The obtained results indicate that a portion of nuts can contribute up to 15% of the recommended daily intake for salt, while for total fat it can reach 27% of the total fat daily intake. The contribution for the daily intake of saturated fatty acids ranged from 2 to 17%, indicating a high variability. In summary, although nuts are a source of healthy fatty acids, it is necessary to carefully evaluate the effects of processing on their nutritional quality, especially due to the addition of salt that is associated with an increase of cardiovascular diseases. Also, this study enhances the importance of nutritional quality of foods to estimate health benefits/risks and the need to develop efforts with food industry to improve the quality and safety of nuts.